A generic privacy ontology and its applications to different domains - Hecker, Michael (Curtin University, 2009)
Privacy is becoming increasingly important due to the advent of e-commerce, but is equally important in other application domains. Domain applications frequently require customers to divulge many personal details about themselves that must be protected carefully in accordance with privacy principles and regulations. Here, we define a privacy ontology to support the provision of privacy and help derive the level of privacy associated with transactions and applications. The privacy ontology provides a framework for developers and service providers to guide and benchmark their applications and systems with regards to the concepts of privacy and the levels and dimensions experienced. Furthermore, it supports users or data subjects with the ability to describe their own privacy requirements and measure them when dealing with other parties that process personal information. The ontology developed captures the knowledge of the domain of privacy and its quality aspects, dimensions and assessment criteria. It is composed of a core ontology, which we call generic privacy ontology and application domain specific extensions, which commit to some of application domain concepts, properties and relationships as well as all of the generic privacy ontology ones. This allows for an evaluation of privacy dimensions in different application domains and we present case studies for two different application domains, namely a restricted B2C e-commerce scenario as well as a restricted hospital scenario from the medical domain.